β-TG and Plasma Catecholamines Levels after Sympathetic Stimuli in Hypertensives and Patients with Peripheral Vascular Disease - Catalano, Maria; Russo, Umberto; Belletti, Sebastiano; Colombo, Fabrizio; Belloni, Armando; Rosso, Gianfranco del; Lombardi, Federico; Libretti, Arnaldo (Thrombosis and Haemostasis, 1990)
The influence of the sympathetic nervous system on platelet functions in vivo is still controversial. The aims of our study were to compare the response to various sympathetic stimuli in normal subjects and in patients with essential hypertension (HT) or peripheral vascular disease (PVD) and to evaluate any correlations among plasma levels of catecholamines, beta-thrombo-globulin (β-TG) and platelet factor 4 (PF4). In basal conditions β-TG and PF4 values in the HT patients were higher than those observed in the controls of the same age but lower than those of the PVD patients. Although the different sympathetic stimuli (90° tilting, handgrip, treadmill test, bicycle test) caused a significant increase of the plasma epinephrine (E) and norepinephrine (NE) levels, they did not modify the β-TG and PF4 levels in any of the groups studied. The platelet activation indices, therefore, regardless of the basal values, do not seem to be influenced by sympathetic stimulation.